The Influence of Brand Image and Lifestyle on Iphone Purchasing Decisions in Cirebon City - Ramadhan, Nauval; Siswanto, Hary; Maulany, Soesanty (International Journal of Business, Economics, and Social Development, 2025)
Background: The development of lifestyle trends and increasingly strong brand image in Indonesia has a major influence on consumer purchasing decisions, especially in the technology product category such as the iPhone. This creates very tight competition in the gadget market. Purpose: This study aims to analyze the influence of lifestyle and brand image on purchasing decisions for iPhone products, especially for consumers in Indonesia. Design/methodology/approach: Product purchasing decisions will be influenced by lifestyle factors and brand image owned by consumers. In this study, primary data were collected using a Likert scale questionnaire. The questionnaire was systematically designed to collect responses relevant to the research topic and consisted of a series of questions distributed to respondents aged 18 to 35 years, with a calculation of the coachran formula of 380 respondents. The data analysis method was carried out using Structural Equation Modeling - Partial Least Square (SEM-PLS). Findings/Results: The results of the study show that lifestyle and brand image have a significant influence on the decision to purchase an iPhone product. Conclusion: This means that these two independent variables together drive the decision to purchase an iPhone, with lifestyle and brand image playing an important role in shaping consumers' desire to purchase the product. Originality/value (State of the art): A modern lifestyle and positive brand image are the main factors that drive the decision to purchase an iPhone product. This shows that consumers choose products based on social identity and brand quality that can meet their lifestyle needs.